KAJIAN POTENSI DAN STRATEGI PENGEMBANGAN OBJEK WISATA CEMORO SEWU DESA KUNGKAI BARU KECAMATAN AIR PERIUKAN KABUPATEN SELUMA - Siti Hanila; Zahrah Indah Ferina (Universitas Prof. Dr. Hazairin SH, 2020)
Cemoro Sewu tourism object managed by The Village Owned Enterprises (BUMDes) BahariSejahtera is one of the many tourist attractions that become local destinations have spertipotential of exotic natural beauty, water rides with rubber boat facilities at the mouth of kungkairiver, Hindu houses of worship such as on the beautiful island of Bali, cool beach air in the firforest, and seafood culinary tourism such as shrimp , shellfish, sea fish and others. Seeing thispotential, the author wants to examine the potential and strategy of developing tourist attractionsFrom the results of IFAS and EFAS contained in chart I layout, SO strategy is a strategy that isconsidered to have high priority and urgent to be implemented are : (1) Create new rides as anopportunity to attract tourists, (2) Increase the intensity of promotion by utilizing all potentialpromotional media to increase interest in tourist arrivals, (3) Maximizing exploration of existingpotentials to meet the needs of tourists. As well as making extensive improvements to supportingfacilities and improving the manager's performance management system in the service, (4)Offering affordable prices provides an opportunity to increase tourism visits, (5) Engage thelocal community to optimize the potential of tourism to provide opportunities for the communityto contribute to the Cemoro Sewu tourism object so that the local community becomes moreproductive to the tourism sector.